Tren Penelitian Penggunaan Artificial Intelligence (AI) dalam Pembelajaran Matematika (Studi Kasus Tahun 2020-2024) - Utami, Rizki Dwi; Hidayat, Mukhlis; Umam, Khairul (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2025)
The rapid development of Artificial Intelligence (AI) technology in mathematics learning has made AI a topic of interest for educational researchers and practitioners. This study aims to identify trends in the use of AI in mathematics education in Indonesia at various levels during the period 2020 to 2024. This research uses a qualitative approach with the Systematic Literature Review (SLR) method to analyse 500 articles indexed in Scopus and Google Scholar. Some of the aspects reviewed include: 1) Year of publication, 2) Author, 3) Methodology, 4) Type of publication, 5) Object of research, and 6) Place of publication. The results showed that 2022-2023 recorded 10 articles, making it the year with the most publications out of a total of 32 articles. Hwang authors accounted for 10% of the total publications, while 75% of the articles used qualitative methodology and 75% were in journal form. Students were the object of most research (53%), followed by teachers (19%). Google Scholar dominated the place of publication (69%). The implications of the study show that the application of AI can improve the personalisation of learning, while emphasising the importance of teacher training and equal access to prevent educational disparities.